Administracinis stilius ir jo sakinio ilgis - Bitinienė, Audronė (Kalbotyra, 1998)
The development of official style in Lithuanian philology has been given due attention despite the previous Russian language influence on it. In recent years the characteristic features of this style have been specified therefore it has become possible to regard it as an autonomous stylistic variety which could be analysed by statistical methods. The official style of the Lithuanian language is not homogeneous; it is represented by four sub-styles, which can be distinguished according to its usage spheres. The frequency and distribution of syntactic constructions are determined on the basis of a corpus consisting 12,000 sentences from four sub-styles of the official style. On average, sentences in Lithuanian official texts are rather long - 34.5 words (s = 38.2 words). The parameters of sentences depend upon the sub-styles, i. e. sentences in legal documents consist of 28.1 words (s = 31.7 words), in diplomacy - 32,1 words (s = 23,4 words), in particular documents - 39,8 words (s = 46.2 words), in normative documents - 37.2 words (s = 44.0 words). Research shows that medium length sentences, consisting of 18-30 words, are most frequently used (32.7%), though of rather frequent use are also long sentences consisting of more than 62 words (18.4%). Sentence length is determined by a sub-style, sentence type and other linguistic factors.